PRASASTI PAṆAI: KAJIAN ULANG TENTANG LOKASI KERAJAAN PAṆAI - Lisda Meyanti (Badan Riset dan Inovasi Nasional, 2019)
Abstract. Paṇai Inscription: Analysis of the Location of Paṇai Kingdom. The Paṇai Inscription was found in the temple complex in Padang Lawas. There is the word